Identification of critical versus robust processing unit operations determining the physical and biochemical properties of cassava‐based semolina (gari) - Escobar, Andrés; Rondet, Eric; Dahdouh, Layal; Ricci, Julien; Akissoé, Noël; Dufour, Dominique; Tran, Thierry; Cuq, Bernard; Delalonde, Michèle (Wiley, 2021)
The gari‐making process involves several unit operations (U.O.), some of which strongly influence the quality of the end product. Two contrasting process scales (laboratory‐scale vs conventional) were compared in order to identify which U.O. were affected by the change of scale. U.O. that changed end‐product characteristics depending on process scale were deemed critical; whereas U.O. that resulted in similar characteristics were deemed robust. The classification depended on quality attributes considered: rasping and roasting were critical for physical properties, in particular particle size which ranged from 0.44 to 0.89 mm between the two process scales; and robust for biochemical properties. In contrast, fermentation and pressing were critical for biochemical properties such as lactic acid content (0.93–1.88 g/100 g dry matter after pressing), which influences the perception of flavour, and robust for physical properties. This classification between critical and robust operations help quality control of gari, by pinpointing which U.O. control specific quality characteristics.